IMC approach to branding Localbrand. - Lin, Esther Peishi. (2008)
LocalBrand is one such company that makes use of T-shirts as a media platform to communicate its brand values and beliefs, which are local and Asian pride. An Integrated Marketing Communications (IMC) approach was used, where various promotional tools were applied to help strengthen the branding of LocalBrand. The key aim was to reach out to the target audience of young adults aged 18 to 35, and inform them about LocalBrand and its philosophy.